LATVIAN FILM MARKETING IN THE INTERNATIONAL MARKET - Cāne, Renāte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The film industry is an important part of the culture of any country and is inseparable from its cultural development and growth, both locally and internationally. Any film created or even its idea is a product which is being promoted and sold on the market similarly as with other types of products. In doing so, many traditional and not-so-convenient communication tools are used in order to reach the required audience and supporters to the viewers for the finished product – the film itself. In order to achieve support and gain popularity, there are certain marketing tools absolutely necessary which are specifically tailored to foster the film promotion. On the international scene, particularly in the major film markets – with the key players being Hollywood, Bollywood and South Korea – it is difficult for the film producers of the smaller countries to break into these markets, therefore a specific approach is needed to attract the attention of supporters and the viewers.Comparatively the Latvian film industry is very small, but this is not a reason why it would be impossible to achieve good results in promotion of films on the international market and attracting supporters. Compared with Estonia and Lithuania, in various indicators Latvia is somewhat lagging behind of its direct neighbours on the international scene. One reason for this is the ineffective use of marketing in order to attract the attention of the international market. The methodology of the research includes analysis of documents and interviews. There were data and statistical rates analyzed from the National Film Centre and five representatives interviewed of the film industry from Latvia. As a result of this research three basic problems appeared that prevented film marketing in Latvia: a lack of understanding the necessity of film marketing, a lack of the film marketing skills and a minimal budget for the industry. In order to promote the development of film marketing in Latvia, there is a necessity to create a film marketing agency that could do a film promotion in the local and in the international level.